2016
DOI: 10.1007/s00221-016-4701-x
|View full text |Cite
|
Sign up to set email alerts
|

Go-stimuli proportion influences response strategy in a sustained attention to response task

Abstract: The sustained attention to response task (SART) usefulness as a measure of sustained attention has been questioned. The SART may instead be a better measure of other psychological processes and could prove useful in understanding some real-world behaviours. Thirty participants completed four Go/No-Go response tasks much like the SART, with Go-stimuli proportions of .50, .65, .80 and .95. As Go-stimuli proportion increased, reaction times decreased while both commission errors and self-reported task-related tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
5
23
1
Order By: Relevance
“…Also, Hartmann et al (2016) reported enhanced activity of the right frontal cortex, including right IFG, in association with top-down IC after Go NoGo task (GNGT) training. GNGT is a mutual task used to assess IC in humans and animals where participants have to respond quickly to frequently occurring 'Go' stimuli and to inhibit responses to infrequent 'NoGo' stimuli (Tamm et al 2002;Swick et al 2008;Luijten et al 2011;Vara et al 2014;Hartmann et al 2016;Wilson et al 2016). Using GNGT, Tamm et al (2002) postulated an association between increasing left IFG activation and response inhibition abilities during development.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Hartmann et al (2016) reported enhanced activity of the right frontal cortex, including right IFG, in association with top-down IC after Go NoGo task (GNGT) training. GNGT is a mutual task used to assess IC in humans and animals where participants have to respond quickly to frequently occurring 'Go' stimuli and to inhibit responses to infrequent 'NoGo' stimuli (Tamm et al 2002;Swick et al 2008;Luijten et al 2011;Vara et al 2014;Hartmann et al 2016;Wilson et al 2016). Using GNGT, Tamm et al (2002) postulated an association between increasing left IFG activation and response inhibition abilities during development.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the interference measure from the Stroop task did not correlate with any of the SART indices. It appears that the SART reflects, firstly, sustained attention rather than response inhibition or at least a different kind of inhibition than that captured by the RT interference index of the Stroop task (for discussion see Carter et al, 2013;Cheyne et al, 2009;Wilson, Finkbeiner, de Joux, Russell, & Helton, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that questions have been raised regarding the extent to which tasks like the SART tax sustained attention versus response inhibition . These alternative perspectives of the not‐X CPT tasks concern the degree to which strategic factors, such as speed–accuracy trade‐offs, are reflected in performance in addition to sustained attention ability . However, others have suggested that both X and not‐X CPT tasks measure overlapping attentional constructs, and recent findings that have shown relationships between performance on the SART and measures of real‐world deficits in sustained attention help to alleviate some of these concerns.…”
Section: Recent Developments In Paradigms To Investigate Sustained Atmentioning
confidence: 99%
“…50 These alternative perspectives of the not-X CPT tasks concern the degree to which strategic factors, such as speed-accuracy trade-offs, are reflected in performance in addition to sustained attention ability. 50,[198][199][200] However, others have suggested that both X and not-X CPT tasks measure overlapping attentional constructs, 24,54,201 and recent findings that have shown relationships between performance on the SART and measures of real-world deficits in sustained attention 51 help to alleviate some of these concerns. We note, however, that this continues to be an active area of debate in the literature.…”
Section: Recent Developments In Paradigms To Investigate Sustained Atmentioning
confidence: 99%